Current perceptions of the UK population regarding the frequency of sports injuries, their long term consequences, particularly osteoarthritis and current care pathways for their management. Issue 15 (10th November 2011) - Grice, A; Conaghan, P G
Abstract : Regular participation in physical activity and sport increases exposure to injury risk. While there are increasing recommendations to exercise or partake in sport, little is known of the frequency of sports injuries for the general public and their understanding of the consequences of such injuries. The aim of this study was to explore the frequency of sports injuries, understanding of their potential consequences and current care pathways for their management. An online survey of 1002 non-elite sports participants explored the hypothesis. The survey recruited physically active participants who exercised three or more times a week. In addition, three 90 min focus group discussions were conducted which included a mix of eight male and female participants aged between 25 and 50 years who trained two, three and four times a week and had suffered a sports related injury during the past two years. The survey revealed that 56% of active participants reported sustaining an injury they believed to be connected to sport or exercise. Participants displayed little or no awareness of osteoarthritis as a long term consequence of sports injuries. Most participants sought advice from general practitioners but they were perceived as gatekeepers to secondary care. More specialised practitioners such as physiotherapists and orthopaedic surgeons are considered more able to effectively treat sports related injuries but long referral times were a problem. Sports and exercise injuries are common among sports participants in the general public. The current lack of awareness of OA as a long term consequence needs to be addressed so sports participants know the importance of engaging in sport in a safe and enjoyable environment. The current perceptions regarding care pathways is that the NHS incurs long referral times with no guarantee of seeing a practitioner who is adequately trained in musculoskeletal medicine when compared to private practice.